Personality traits and college students' internet addiction: The mediating roles of general health and self‐esteem. Issue 6 (15th June 2022) - Khosravi, Mohsen; Khosrobaki, Masumeh; Foroutan, Aida
Abstract : This research aimed to explore the gender‐related differences in Internet addiction levels, the associated factors behind Internet addiction, and the mediating roles of general health and self‐esteem in the relationship between personality traits and Internet addiction among college students. A total of 318 college students in Iran participating in this study completed sociodemographic information form and self‐report measures of Internet addiction, personality traits, general health, and self‐esteem. The results showed higher frequencies of low and moderate–severe levels of addiction among female and male students, respectively. Further, younger age, male gender, singleness, high scores on neuroticism, poor general health, and low self‐esteem might be linked to Internet addiction. The overall hypothesis that general health and self‐esteem mediated the effect of neuroticism on Internet addiction was also supported. Our findings highlighted the necessity of evaluating general health and self‐esteem among Internet‐addicted students. Further, these variables can be targeted by psychiatrists and psychologists for effective cognitive‐behavioral therapy among Internet‐addicted students.